Comparative In Vitro Antifungal Activity of 0.2% Chlorhexidine Gluconate and 1% Povidone-Iodine Oral Antiseptic Solutions Against Candida albicans - Jorgy Rahmat Syahhada; Rahayu Rahayu; Conita Yuniarifa; Mohamad Arif; Masfiyah Masfiyah (Journal of Advanced Multidisciplinary Research, 2026)
Alterations in the oral microbiota of mechanically ventilated intensive care unit (ICU) patients increase the risk of Candida albicans colonization, which may contribute to prolonged hospitalization and higher morbidity. Chlorhexidine gluconate and povidone-iodine are commonly used oral antiseptics; however, direct evidence comparing their antifungal activity at clinically used concentrations remains limited. This study compared the in vitro antifungal activity of 0.2% chlorhexidine gluconate and 1% povidone-iodine against Candida albicans. This laboratory experimental study used a post-test-only control group design. Antifungal activity was assessed using the Kirby–Bauer disk diffusion method with a standardized Candida albicans suspension adjusted to the 0.5 McFarland standard. Sterile normal saline served as the negative control. Inhibition zone diameters were measured after 24 hours of incubation at 37°C. Data from 20 replicates per group were analyzed using the Mann–Whitney U test. The 0.2% chlorhexidine gluconate group produced a significantly larger median inhibition zone than the 1% povidone-iodine group [20 mm (range, 19–20 mm) vs. 11 mm (range, 10–11 mm); p < 0.001], while the negative control showed no inhibition. These findings indicate that 0.2% chlorhexidine gluconate has greater in vitro antifungal activity against Candida albicans than 1% povidone-iodine. Further MIC/MFC, biofilm-based, and clinical studies are recommended.